Preliminary Results from Archaeological Investigations on Avayalik Island, Extreme Northern Labrador - Jordan, Richard H. (ARCTIC, 1980)
Archaeological investigations on Avayalik Island near the tip of the Labrador Peninsula by the Torngat Archaeological Project have produced data crucial to a new, but preliminary, understanding of Middle Dorset tool kits, subsistence pursuits, settlement patterns, house forms, and technological changes from Early to Middle Dorset. Three sites, tentatively dated to the early Middle Dorset period, demonstrate a gradual evolution from Early to Middle Dorset registered in the lithic remains. They also exhibit a variety of house forms and associated features suggesting seasonal and/or functional differences. The fourth site discussed, Avayalik-1, consists of a deep midden deposit whose lowest levels are nearly perfectly preserved. Wood artifacts are numerous and suggest that this raw material played an extremely important role in Dorset technology. Faunal evidence from this site, combined with evidence from other sites, indicates a summer to early winter focus on birds and seals, particularly the migratory harp seal at ice-edge and outer island locales such as Avayalik. The importance of these new adaptive patterns, compared to earlier groups is discussed.